(untitled) (TAJ: Journal of Teachers Association, 2022)
Background: Carbapenem resistance is a major and ongoing public health problem globally and locally. It occurs mainly among Gram-negative pathogens such as Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. Most of the carbapenemase-producing bacteria are multidrug resistant, including 3rd generation of cephalosporin and carbapenems. It may be intrinsic or mediated by transferable carbapenemase-encoding genes. This type of resistance gene is already widespread in certain parts of the world, mainly Europe, Asia, and South America. Objective: To isolate and identify WHO-declared carbapenemase-producing deadliest drug resistance bacteria with their antibiogram in the Rajshahi region. Materials Method: Cross sectional descriptive study was done from July 2017 to June 2018. Wound swab was collected in different surgical and burn units of Rajshahi Medical College Hospital. The specimens were inoculated in blood agar, nutrient agar, and MacConkey’s agar media and incubated aerobically at 370 C for 24 hours. Susceptibility tests of the bacterial isolates were done by using the modified Kirby Bauer disk diffusion method on Mueller Hinton agar media. Carbapenemase-producing bacteria were identified by using the modified Hodge test. Results: Out of the total 250 samples, culture yielded growth in 213(85.2%) cases, and 37(14.8%) yielded no increase. Females were predominant 146(58.4%) in comparison to males 104(41.6%), with a male-female ratio of 1: 1.4. A maximum of 47.2% of cases were between 19-30 years old. Among the culture-positive isolates, gram-negative organisms were higher (58.8%) than gram-positive (41.2%). S. aureus was the predominant organism 71(30.8%), followed by P. aeruginosa 47(20.3%), E.coli 43(18.7%), and Acinetobacter baumannii 07 (3%). Among seven isolated Acinetobacter baumannii, 47 isolated P. aeruginosa, and 82 isolated Enterobacteriaceae: 6(85.7%), 33(70.2%), and 53(64.6%) were MDR; and 4(57.1%), 12(25.5%) and 14(17%) were carbapenemase-producers respectively. Conclusion: Most of the isolated carbapenemase-producing bacteria are multidrug resistant, and they tend to cause complicated infections. In addition, the expression of specific virulent factors, difficulty in diagnosis, and the non-availability of newer generation antibiotics make them one of the deadliest bacteria. TAJ 2022; 35: No-1: 91-98